PENYULUHAN STUNTING KELILING DI DESA CINTABODAS - Muharry, Andy; Roja, Elva Na’imatu; Agustin, Sifa; Fadilah, Yulis Ramdhan; Fadila, Della; Rifkiyandi, Muhammad Rifan; Yusuf, Muhammad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
The prevalence of stunting in children under the age of 5 is one of Indonesia's main nutritional problems. Based on the reported stunting data, there were 30 cases in Cintabodas Village. This community service activity aims to strengthen the independence of Posyandu officers in Cintabodas village in monitoring stunted children. In addition, this activity also aims to increase knowledge for parents, especially mothers who have children under five and pregnant women who have problems with stunting and malnutrition. This community service is carried out with cadres at each Posyandu in the village. The door-to-door Posling (Mobile Posyandu) activities ran smoothly with the enthusiasm of the participants. Based on the results of the assessment through filling out the pre-test and post-test, it can be seen that there is an increase in the mother's knowledge. This activity was well received by mothers with babies and toddlers as well as pregnant women.